Inflammaging: triggers, molecular mechanisms, immunological consequences, sex differences, and cutaneous manifestations - Karpuzoglu, Ebru; Holladay, Steven D.; Gogal, Robert M. (Frontiers in Immunology, 2025)
Inflammaging, defined as chronic, low-grade, systemic inflammation that increases with age in the absence of overt infection, is a phenomenon that was first described in 2000 as a member of a growing number of age-related processes that had pleiotropic effects on immune function and disease susceptibility. Although many pathological consequences have been attributed to inflammaging, it remains distinct from immunosenescence and not completely understood. A resurgence of interest in inflammaging has been spurred by recent work demonstrating roles for senescent cells in driving chronic inflammatory signaling and defining the cellular and molecular triggers that sustain cytokine production during aging. Alongside elevations in pro-inflammatory mediators (e.g., IL-6, TNF-α, IL-1β), attention to anti-inflammatory mediators (e.g., IL-10, IL-1Ra) and composite ratios (e.g., IL-6:IL-10) can better index inflammatory balance in older adults. In this review, we summarize the characterization of inflammaging mechanisms, highlight roles for chronic inflammation that are clearly defined in immune system remodeling, and outline questions regarding inflammaging functions in sex differences, hormonal regulation, autoimmunity, and skin biology that still require further exploration.